Development of Student Worksheets Containing Ethnomathematics as Mathematics Teaching Materials for Class X of SMAN 1 Tulungagung - Rangga, Ardiansyah Dwi; Ramadani, Putra Trio; Lestari, Rahmadhani Eka (CV. Ihsan Cahaya Pustaka, 2025)
Mathematics learning in secondary schools often remains abstract and insufficiently connected to students’ cultural contexts, which can limit engagement and problem-solving skills; therefore, ethnomathematics offers a meaningful approach by linking mathematical concepts with local cultural practices. This study aimed to develop and evaluate the validity, practicality, and effectiveness of ethnomathematics-based Student Worksheets (LKPD) on geometry for Grade X students at SMAN 1 Tulungagung. The research employed a Research and Development (R&D) method using the 4-D model, consisting of the Define, Design, Develop, and Disseminate stages, in which the LKPD were designed by integrating local cultural elements of Batik Reog Kendang Tulungagung into geometry learning activities. The results showed that expert validation achieved a Content Validity Index (CVI) of 0.86, indicating very high validity, while practicality assessments from teachers and students yielded an average score of 89%, categorized as very good. Furthermore, post-test results demonstrated that 84.38% of students met the minimum mastery criterion, supported by classroom observations that revealed increased student engagement and active participation. In conclusion, the ethnomathematics-based LKPD developed in this study are valid, practical, and effective, providing a culturally responsive instructional approach that enhances students’ conceptual understanding and mathematical problem-solving abilities in geometry learning.